2019
DOI: 10.3389/fnhum.2019.00256
|View full text |Cite
|
Sign up to set email alerts
|

Action Semantic Deficits and Impaired Motor Skills in Autistic Adults Without Intellectual Impairment

Abstract: Several studies indicate the functional importance of the motor cortex for higher cognition, language and semantic processing, and place the neural substrate of these processes in sensorimotor action-perception circuits linking motor, sensory and perisylvian language regions. Interestingly, in individuals with autism spectrum disorder (ASD), semantic processing of action and emotion words seems to be impaired and is associated with hypoactivity of the motor cortex during semantic processing. In this study, the… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
7
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
4
3

Relationship

0
7

Authors

Journals

citations
Cited by 10 publications
(8 citation statements)
references
References 96 publications
(152 reference statements)
1
7
0
Order By: Relevance
“…We also observed reduced intra-connectivity in the PCC and increased intra-connectivity in precuneus for both illnesses, aligning with previous findings 36 . Interestingly, we revealed that the integration within the SM domain was also diminished in both disorders, supporting their SM abnormality [43][44][45][46] .…”
Section: Discussionsupporting
confidence: 65%
“…We also observed reduced intra-connectivity in the PCC and increased intra-connectivity in precuneus for both illnesses, aligning with previous findings 36 . Interestingly, we revealed that the integration within the SM domain was also diminished in both disorders, supporting their SM abnormality [43][44][45][46] .…”
Section: Discussionsupporting
confidence: 65%
“…These results are consistent with those obtained by Inokuchi and Kamio (105), who found a deficit in the semantic clustering process in VFT in autistic adults compared to NT controls. A decrease in the number of action names spontaneously generated could be caused by executive dysfunction 10.3389/fpsyt.2023.1098210 (105), motor impairment (108), or deficits in social cognition in ASD and ADHD. In addition, the performance of adults with ADHD in this task was correlated with an unconstrained VFT condition (the free condition; Table 6) which is particularly dependent on initiation strategies.…”
Section: Discussionmentioning
confidence: 99%
“…In view of results from a previous study on co-occurring ADHD + ASD ( 97 ), this group may present with the emotional particularities of both conditions with emotion generation difficulties related to joy, fear and anger. Regarding AVFT, given the primary deficits in predicting, and interpreting the actions of others ( 107 ), and motor issues involving fronto-striatal circuits ( 108 ) in ASD, adults with ADHD + ASD are expected to produce fewer and rarer (low frequency in the language) action verbs than adults with ADHD and NT controls, whereas adults with ADHD will produce fewer action verbs than NT adults. Nevertheless, due to the hyperactivity found in ADHD, the action verbs produced are expected to be more arousing than those found in NT.…”
Section: Introductionmentioning
confidence: 99%
“…Since the discovery of mirror neurons (Gallese et al, 1996;Rizzolatti et al, 1996), that react similarly for goal-oriented self-motions and for similar motions of others and thus allow estimations of the intentions of others, scientists have considered that the mirror neuron system may be impaired or possibly dysfunctional in autism, see, e.g., (Williams et al, 2001;Rizzolatti and Fabbri-Destro 2010;Hillus et al 2019, and the cited references therein). It was thought that in typical cases, mirror neurons can provide supervisory information for training and for copying behavioral templates.…”
Section: 'Mirror Neuron Theory'mentioning
confidence: 99%